O transbordo de granéis sólidos nos portos marítimos do sul do Brasil: análise sob a ótica da eficiência logística - Pinela, Sandra Regina da Silva (2018)
International trade in goods and services has grown significantly along the 2,000s decade and kept up in recent years. Maritime transport accounted for 80% of foreign trade operations in 2013, which implies specialized locations to move and transship goods, with maritime ports being strategic points in the global logistics chain. In Brazil, the agricultural sector is the main product in the trade balance, in which agricultural bulk is the busiest product in ports.Yet, 64% of the total produced in the country is concentrated in the states of Mato Grosso, Parana and Rio Grande do Sul, which send a large part of the shipments to the ports of the Southern Region of Brazil. This type of cargo is characterized by large volumes, and low added value. As a result, the port facilities seek to operate quickly and safely. Thus, the present study aims to analyze the technical efficiency of the southern Brazilian seaports by means of Data Envelopment Analysis (DEA), focusing on the logistic activity of transshipment of solid bulk in the dock area, to identify possible inefficiencies. For this, the theoretical assumptions and parameters on logistics and technical efficiency were used. The empirical data, which comprise the period from 2010 to 2016, were obtained through a survey of the Management Information System (GIS) of the National Waterway Transportation Agency (Antaq), and consult the reports of the Master Plan of the Ports Secretariat of the Presidency of the Republic (SEP/PR). Also, in July and August, 2016, there were technical visits in Paranaguá and São Francisco do Sul ports and unstructured interviews with their managers were carried out. The variables of DEA Model were determined by the statistical method Principal Component Analysis (PCA) which proved to be effective for the reduction of variables, in order to meet the proportionality requirement of the DEA model, as well as to solve the problem of the presence of outliers. The DEA-BCC method proved to be adequate to measure port efficiency, by considering scale variation, not assuming proportionality between inputs and outputs, and being a more realistic approach than DEA-CCR. The main results showed that there is a hierarchical structure for the operation of Brazilian seaports, shaped by the institutional environment, whose regulation is delimited by the Executive Branch Act and the management of the activities is carried out by port operators. Transshipment in the dock area was considered a critical stage in international physical distribution logistics. The determining factor of inefficiency of these ports was the high length of stay of ships. To achieve 100% efficiency, ports need to increase the number of berths and for this to happen, and for that to happen, management strategies or asset investments are needed to improve the speed of transshipment. The gain in efficiency of the ports of the South of Brazil will allow greater competition with the others and will provide greater development of the region.